Analisis Persediaan Bahan Baku pada Bakso Atmo Karawang - Marlyn Diva Christina; Dedi Mulyadi; Santi Pertiwi Hari Sandi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the management of raw material inventory at the Bakso Atmo Karawang SME during the study period. The method used was quantitative descriptive analysis with a saturated sampling technique, allowing for a comprehensive analysis of all available data. The results indicate that Bakso Atmo Karawang implements a daily raw material ordering system through partnerships with regular suppliers without maintaining a reserve inventory. Inventory management is conducted using the First In First Out (FIFO) method to maintain the quality and freshness of raw materials and minimize the risk of spoilage. Raw material requirements during the study period tended to be stable but experienced increases at certain times due to rising demand, such as during holidays and the year-end break. This increase in demand resulted in higher raw material purchase costs. The implemented inventory system has proven to be simple, consistent, and effective in supporting the smooth production process and maintaining product quality. This study provides practical contributions to SME operators in improving the efficiency and effectiveness of raw material inventory management.